Does the construction of innovative cities promote urban green innovation?. (15th September 2022) - Li, Lei; Li, Mingqi; Ma, Shaojun; Zheng, Yilin; Pan, Chenzi
Abstract: As a typical example of an innovative governance environment, innovative city has become the focus of political and academic circles. Discussing the green innovation effect of this policy is beneficial in providing decision support for enhancing urban green innovation capability and solving the dilemma of urban resources. Based on data from 241 cities in China from 2005 to 2017, this paper takes innovative city construction as a "quasi-natural experiment" and uses the difference-in-differences method to empirically study the impact of China's innovative city construction on urban green innovation. The results show that innovative urban construction: has a positive effect on improving urban green innovation, and that this effect will gradually increase with time; promotes urban green innovation by expanding the scope of technology application, improving the efficiency of resource allocation and promoting the adjustment of industrial structure; and presents heterogeneity in cities' location, size and hierarchy. Finally, this paper proposes that the government should promote innovative policies in an orderly manner on the basis of following the principle of adapting measures to local conditions, as well as incorporating green innovation performance into the evaluation system for innovative city construction. Highlights: Innovative city has a continuous positive impact on urban green innovation. Three impact paths of innovative cities on urban green innovation are proposed. The effect of green innovation is more obvious in the central and western regions. The city size and green innovation effect develop in an inverted U shape. Cities with higher hierarchy show stronger response to the green innovation effect.